Single phase and two phase flow for heat transfer in micro channel heat sink - Shkarah, Ahmed Jassim (UTeM, 2016)
Advancements in microprocessors and other high power electronics have resulted in increased heat dissipation from those devices. In addition, to reduce cost, the functionality of microprocessor per unit area had been increasing. The increase in functionality accompanied by reduction in chip size had caused its thermal management to be challenging. In order to dissipate the increase in heat generation, the size of conventional microchannel heat sinks had to be increased. As a result, the performance of these high heat flux generating electronics was often limited by the available cooling technology and space to accommodate the larger conventional microchannel heat sink. One way to enhance heat transfer from electronics without sacrificing their performance was the use of heat sink with many microchannels and liquid passing through it recently, the microchannel heat sink have been widely used to transfer heat from the microprocessors in the computer industry. As the heat flux increases, the thin film evaporation occurring in the evaporator plays a key role in a heat transfer. It had been shown that most of the heat input to the evaporator of the microchannel heat sink was transferred through the evaporating thin film region. A better understanding of heat transfer characteristics in the evaporating thin film region will lead to develop new equation in the thin film region and enhancing the evaporating heat transfer in the heat pipe. An analytical model describing thin film evaporation was developed including the thin film interface and disjoining pressure. A mathematical equation was then developed to investigate the effect of heat flux on film thickness in the thin film evaporation region. Results are provided for liquid film thickness, total heat flux, and evaporating heat flux distribution. In addition to the sample calculations that were used to illustrate the transport characteristics. The calculated results from the current model match closely with those of analytical results of Wang et al. (2008) and Wayner jr. et al. (1976). This work will lead to a better understanding of heat transfer and fluid flow occurring in the evaporating film region and develop an analytical equation for evaporating liquid film thickness.numerical analysis and experimental tests to predict the heat transfer and chf are the focus of this work. The experimental test section had three microchannels with having of 30 mm x 25.4 mm x 53.34 mm in size. The effect of flow instabilities in microchannels was investigated of each microchannel to stabilize the water flow boiling process. Water flow boiling was investigated in this study using degassed, deionized water in an aluminum, copper and a graphene rectangular microchannel with a hydraulic diameter of 540 μm and 426 μm for Re 650-3000. The power input was adjusted for constant heat flux (630-520) kw/m2 for each flow rate. High speed images were taken periodically for water flow boiling. The change in regime timing revealed the effect of deposition on the onset of nucleate boiling (ONB) cycle duration and bubble frequencies are reported for different flow boiling durations. The addition bubble formation was found to stabilize bubble nucleation and growth and limit the recession rate of the upstream and downstream interfaces, mitigating the spreading of dry spots and elongating the thin film regions to increase thin film evaporation.